2019
DOI: 10.1155/2019/4852706
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolcanic Carbon Dioxide Emission at Continental Rifts: The Bublak Mofette Area, Western Eger Rift, Czech Republic

Abstract: This study presents the results of gas flux measurements of cold, mantle-derived CO2 release at the Bublák mofette field (BMF), located inside of the N-S directed Počátky Plesná fault zone (PPFZ). The PPFZ is presently seismically active, located in the eastern part of the Cheb Basin, western Eger Rift, Central Europe. The goal of the work was to identify the linkage between tectonics and gas flux. The investigated area has a size of 0,43 km2 in which 1.115 locations have been measured. Besides classical soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…1, 2). The western part of the WSW-ENE-trending Eger Rift, particularly the Cheb Basin, which formed along NNW-SSEtrending faults (Špičáková et al 2000;Rojik et al 2014), is at present the most active geodynamic region in the European Cenozoic Rift System (ECRIS) with a high number of earthquake swarms at least in the last 40 years (Fischer et al 2014;Vavryčuk and Adamová 2018) as well as mantlederived CO 2 -degassing (Weinlich et al 1999;Bräuer et al 2009Bräuer et al , 2014Kämpf et al 2013Kämpf et al , 2019Nickschick et al 2015). The progressive increase of the He 3 /He 4 ratio at the eastern part of the Cheb Basin since about 2000 with shorttime peaks up to 6.3 R a in 2000 and 2006 at the Bublák mofette indicates an ascent of less degassed magma (dyke intrusion) from the lithospheric mantle reservoir into the crust (Bräuer et al 2009(Bräuer et al , 2018.…”
Section: Geodynamic Setting and Previous Investigationsmentioning
confidence: 99%
“…1, 2). The western part of the WSW-ENE-trending Eger Rift, particularly the Cheb Basin, which formed along NNW-SSEtrending faults (Špičáková et al 2000;Rojik et al 2014), is at present the most active geodynamic region in the European Cenozoic Rift System (ECRIS) with a high number of earthquake swarms at least in the last 40 years (Fischer et al 2014;Vavryčuk and Adamová 2018) as well as mantlederived CO 2 -degassing (Weinlich et al 1999;Bräuer et al 2009Bräuer et al , 2014Kämpf et al 2013Kämpf et al , 2019Nickschick et al 2015). The progressive increase of the He 3 /He 4 ratio at the eastern part of the Cheb Basin since about 2000 with shorttime peaks up to 6.3 R a in 2000 and 2006 at the Bublák mofette indicates an ascent of less degassed magma (dyke intrusion) from the lithospheric mantle reservoir into the crust (Bräuer et al 2009(Bräuer et al , 2018.…”
Section: Geodynamic Setting and Previous Investigationsmentioning
confidence: 99%
“…The CO 2 originates from active magma chambers at the crust-mantle boundary and from lithospheric mantle depths of about 65 km (Heuer et al, 2006 ; Bräuer et al, 2009 ). The CO 2 preferentially migrates to the surface as component of supercritical fluids in the lower crust or either dissolved in water or as a free gas phase along deep-seated faults in the upper crust (Weinlich et al, 1999 ; Weise et al, 2001 ; Bräuer et al, 2011 ; Kämpf et al, 2019 ). The PPZ started to develop at the boundary from Mid to Late Pleistocene (Bankwitz et al, 2003a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations from sediments of the upper 9 m at the Hartoušov mofette system revealed that ascending CO 2 -containing fluids cause sediment fluidization, hydrofracturing, and geochemical alterations e.g., sediment bleaching, mobilization of metals and the preservation of organic matter (Flechsig et al, 2008 ; Rennert et al, 2011 ; Mehlhorn et al, 2016 , 2018 ; Rennert and Pfanz, 2016 ; Bussert et al, 2017 ; Liu et al, 2018 ). At the surface, CO 2 exhalation occurs in form of diffuse degassing structures (DDS, namely dry mofettes) and localized water filled, pool-like structures (wet mofettes) (Flechsig et al, 2008 ; Kämpf et al, 2013 , 2019 ; Nickschick et al, 2015 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate relationships between geodynamic processes, CO 2 degassing, and the continental "deep biosphere, " three boreholes were drilled in the intensively degassing HMF (Dahm et al, 2013, 26 t/d of diffuse soil degassing; Kämpf et al, 2019). F1 [corresponding to 1H-031 in Bräuer et al (2018) andVP8303 in Fischer et al (2020)] was drilled in 2007 down to ∼28 m below ground and taps into a CO 2saturated, confined aquifer.…”
Section: Study Areamentioning
confidence: 99%